2020
DOI: 10.1111/nep.13835
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations by the Asian Pacific society of nephrology (APSN) on the appropriate use of HIF‐PH inhibitors

Abstract: Renal anaemia is a common and important complication in patients with chronic kidney disease (CKD). The current standard‐of‐care treatment for renal anaemia in CKD patients involves ensuring adequate iron stores and administration of erythropoietin stimulating agents (ESA). Hypoxia inducible factor (HIF) is a key transcription factor primarily involved in the cellular regulation and efficiency of oxygen delivery. Manipulation of the HIF pathway by the use of HIF‐prolyl hydroxylase inhibitors (HIF‐PHI) has emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 94 publications
2
76
1
8
Order By: Relevance
“…Recent recommendations by the Asian Pacific Society of Nephrology emphasized the importance of avoiding excessive serum iron lowering by HIF-PHIs to minimize the risk of associated adverse effects. 181 Additional areas of uncertainty. Several mechanistic knowledge gaps and high-priority research areas regarding HIF-PHIs were identified (Table 1).…”
Section: The Impact Of Esas and Novel Therapeutic Agents On Hemoglobin Control Iron Status And Iron Supplementation Needs Iron In Currentmentioning
confidence: 99%
“…Recent recommendations by the Asian Pacific Society of Nephrology emphasized the importance of avoiding excessive serum iron lowering by HIF-PHIs to minimize the risk of associated adverse effects. 181 Additional areas of uncertainty. Several mechanistic knowledge gaps and high-priority research areas regarding HIF-PHIs were identified (Table 1).…”
Section: The Impact Of Esas and Novel Therapeutic Agents On Hemoglobin Control Iron Status And Iron Supplementation Needs Iron In Currentmentioning
confidence: 99%
“…It remains to be seen whether such selectivity affects the malignancy risk of individual PHDs. Among various drugs that have been developed, at least five HIF-PHIs, approved for the treatment of renal anemia in Japan, are being used in clinical practice as of 2021 [ 24 ].…”
Section: Development Of Hif-phis For Clinical Usementioning
confidence: 99%
“…Absorption of orally administered HIF-PHIs from the intestinal tract can result in HIF activation in most cells in the body. HIF-PHIs are clinically used for the treatment of renal anemia [ 24 , 25 , 113 ].…”
Section: Hif-phis As a Treatment For Renal Anemiamentioning
confidence: 99%
See 2 more Smart Citations